Significant weight loss and hypernatremia in exclusively breast-fed neonates - Jayaraj, Daniel; Kumar, Poornima; Kommu, Peter Prasanth Kumar; Krishnan, Lalitha (International Journal of Contemporary Pediatrics, 2017)
Background: Weight loss in the early neonatal period is a problem that often goes unrecognized. Weight loss of upto 5-7% of birth weight is normal but losses more that 10% may result in increased morbidity, especially hypernatremia. Methods: Prospective cohort study of 900, exclusive breastfed inborn babies, >34 weeks gestation and >1800g born in a tertiary care hospital in South India. Babies who were discharged before 96 hours of life, admitted to intensive care and received phototherapy for >24hrs were excluded. Maternal and neonatal variables were collected, and daily weight loss percent was calculated. Data was entered in EPI-INFO and analysed. Independent sample t test was used to compare the means of two independent normally distributed sample groups, ANOVA was used to compare means of more than 2 variables, linear logistic regression was used to find out the relationship between significant weight loss and hypernatremia Results: The mean birth weight of the cohort was 2937±438.4 g and the gestational age was 38±5weeks. The mean maximum weight loss for the entire cohort was 178.71g (±82.08 g) and the mean percent weight loss was 6.12% (2.69). The mean weight nadir of the entire cohort was 2758.32±425.67g. Mean serum sodium levels for all babies who lost >10% of their birth weight was 145.95 (±2.34) mmol/L Conclusions: Early neonatal weight loss is a universal phenomenon though often unrecognized. Babies losing more than 10% of birth weight are at risk of morbidities like hypernatremia.